Ovarian fluid proteome variation associates with sperm swimming speed in an externally fertilizing fish. (25th October 2020) - Johnson, Sheri L.; Borziak, Kirill; Kleffmann, Torsten; Rosengrave, Patrice; Dorus, Steve; Gemmell, Neil J.
Abstract: Sperm velocity is a key trait that predicts the outcome of sperm competition. By promoting or impeding sperm velocity, females can control fertilization via postcopulatory cryptic female choice. In Chinook salmon, ovarian fluid (OF), which surrounds the ova, mediates sperm velocity according to male and female identity, biasing the outcome of sperm competition towards males with faster sperm. Past investigations have revealed proteome variation in OF, but the specific components of OF that differentially mediate sperm velocity have yet to be characterized. Here we use quantitative proteomics to investigate whether OF protein composition explains variation in sperm velocity and fertilization success. We found that OF proteomes from six females robustly clustered into two groups and that these groups are distinguished by the abundance of a restricted set of proteins significantly associated with sperm velocity. Exposure of sperm to OF from females in group I had faster sperm compared to sperm exposed to the OF of group II females. Overall, OF proteins that distinguished between these groups were enriched for vitellogenin and calcium ion interactions. Our findings suggest that these proteins may form the functional basis for cryptic female choice via the biochemical and physiological mediation of sperm velocity. Abstract : In many species females can bias sperm use towards a preferred male, but the underlying mechanisms remain poorly understood. Here we use proteomics to explore how salmon ovarian fluid (OF) protein variation influences sperm swimming speed. We show that females cluster into two groups (A) and that exposure of sperm to OF from females in group I had faster sperm compared to sperm exposed to the OF of group II females (B). These groups are distinguished by the abundance of a set of proteins associated with sperm velocity, establishing a subset of proteins that warrant further examination.